Bioctive glycoglycerolipid analogues: an expeditious enzymatic approach to mono- and diesters of 2-O-beta-D-galactoglycerol - D. Colombo; F. Ronchetti; A. Scala; TOMA, LUCIO (Tetrahedron: Asymmetry, 1998)
2-O-beta-D-Galactosylglycerol 1 was submitted to acylation using Pseudomonas cepacia or Candida antarctica lipases as catalysts and 2,2,2-trifluoroethyl esters of butanoic, hexanoic, octanoic or decanoic acid as acyl carriers. Taking advantage of the high diastereoselectivity and regioselectivity of the two enzymes, the 1-O-, 3-O-, 6'-O-acyl and the 1,6'-di-O-acylderivatives of 1 were obtained pure or in an appreciably enriched form. (C) 1998 Elsevier Science Ltd. All rights reserved.